Can Labelling Create Transformative Food System Change for Human and Planetary Health? A Case Study of Meat - Christine Parker; Rachel Carey; Fiona Haines; Hope Johnson (Kerman University of Medical Sciences, 2021)
BackgroundOne important way to transform food systems for human and planetary health would be to reduce the production and consumption of animals for food. The over-production and over-consumption of meat and dairy products is resource-intensive, energy-dense and creates public health and food equity risks, including the creation of superbugs and antimicrobial resistance, contamination and pollution of land and waterways, and injustice to animals and humans who work in the sector. Yet the continuing and expanding use of animals is entrenched in food systems. One policy response frequently suggested by parties from all sectors (industry, government and civil society) is voluntary or mandatory labelling reforms to educate consumers about the healthiness and sustainability of food products, and thus reduce demand. This paper evaluates the pitfalls and potentials of labelling as an incremental regulatory governance stepping-stone to transformative food system change. MethodsWe use empirical data from a study of the regulatory politics of animal welfare and environmental claims on Australian products together with an ecological regulation conceptual approach to critically evaluate the potential of labelling as a regulatory mechanism. ResultsWe show that labelling is generally ineffective as a pathway to transformative food system change for three reasons: it does not do enough to redistribute power away from dominant actors to those harmed by the food system; it is vulnerable to greenwashing and reductionism; and it leads to market segmentation rather than collective political action. ConclusionWe suggest the need for regulatory governance that is ecological by design. Labelling can only be effective when connected to a broader suite of measures to reduce overall production and consumption of meat. We conclude with some recommendations as to how public health advocates and policy entrepreneurs might strategically use and contest labelling and certification schemes to build support for transformative food system change and to avoid the regressive consequences of labelling.